PERKAWINAN LARI BERSAMA DAN PERKAWINAN BAWA LARI PADA MASYARAKAT ADAT SEBAGAI SUATU BENTUK PELANGGARAN ADAT - Padlan Zamzimi (Jurnal LEX SPECIALIS, 2010)
Costumary law system is a traditional law system that living in Indonesia peopleas apart of culture, the difference to the national law is about the codification, codification costumary law system is unwritten and codification national law system is written but also costumary law system is unwritten legality of binding law is same like written law, because the is acknowlwdge in Indonesia legal system, one most controversial costumary law system is abou marital law in this journal it will be explain about costumary law system in marital Key Note: Costumary law system in costumary people